THE ROLE OF SPIRITUAL HERITAGE OF WESTERN AND EASTERN PEOPLE IN YOUTH EDUCATION (American Journal of Interdisciplinary Research and Development, 2023)
In this article, the use of the national spiritual heritage of the Eastern and Western nations in the education of young people, the education of young and talented representatives who can meet the needs of the nation and the world's requirements, and the formation of a new national ideology, the people's ma It was stated about the need to raise the morale.